Identification of a gene involved in the regulation of hyphal growth of Epichloë festucae during symbiosis. Issue 19 (12th September 2016) - Bassett, Shalome A.; Johnson, Richard D.; Simpson, Wayne R.; Laugraud, Aurelie; Jordan, T. William; Bryan, Gregory T.
Abstract : Secreted proteins, those involved in cell wall biogenesis, are likely to play a role in communication in the symbiotic interaction between the fungal endophyte Epichloë festucae with perennial ryegrass ( Lolium perenne ), particularly given the close association between fungal hyphae and the plant cell wall. Our hypothesis was that secreted proteins are likely to be responsible for establishing and maintaining a normal symbiotic relationship. We analyzed an endophyte EST database for genes with predicted signal peptide sequences. Here, we report the identification and characterization of rhgA ; a gene involved in the regulation of hyphal growth in planta . In planta analysis of Δ rhgA mutants showed that disruption of rhgA resulted in extensive unregulated hyphal growth. This phenotype was fully complemented by insertion of the rhgA gene and suggests that rhgA is important for maintaining normal hyphal growth during symbiosis. Abstract : Identification and characterization of rhgA, a gene important for maintaining a symbiotic relationship between beneficial fungal endophytes and their plant hosts.